Digital Book Development as Teaching Material for Computer Accounting Practicum Using Accurate Software - Fauzan, Slamet; Wardoyo, Cipto Wardoyo; Izzalqurny, Tomy Risky; Moliani, Ayuneng Indah; Andryani; Narmaditya, Bagus Shandy (Economic Education Analysis Journal, 2024)
Accurate is an alternative accounting software besides MYOB that can be used to support the learning and teaching in the accounting computer. This research aims to develop an Accurate digital book. This study adopted research and development model and Borg and Gall, which consists of research and initial data collection, planning and development, expert and user validation, revision, field testing, and finished product. The findings indicate that the Accurate digital book developed by the researcher was considered very feasible by material experts, media experts, and limited users. In addition, the Accurate digital book is also considered effective in increasing user understanding of the application of Accurate. Therefore, it is suggested to involve this digital book for accounting computer.